SYARAT DAN ETIKA MUFASIR - Nurhidayah, Nurhidayah; Rachman, Syaiful (Jurnal Multidisipliner Kapalamada, 2024)
Interpreting the Koran is a task that requires deep expertise and high morality. This article reviews the various requirements and ethics that a mufasir must have so that the resulting interpretation is in line with Islamic law and the needs of society. These requirements include mastery of basic knowledge such as Arabic, ulumul Qur'an, hadith, ushul fiqh, as well as an understanding of historical and social context. Apart from that, a mufasir is required to have strong faith, sincere intentions, and dedication to the truth. From an ethical point of view, honesty in knowledge, a humble attitude, and respect for the interpretive works of previous scholars are the fundamental principles. This article emphasizes that fulfilling these requirements and ethics can have a positive impact in explaining and applying the teachings of the Koran to the lives of Muslims at large.